A calculator for valorizing bauxite residue in the cement industry - Michael Di Mare (Elsevier, 2021)
A computational tool using Microsoft Excel was developed to identify opportunities to repurpose bauxite residue as a raw material in the production of Portland cement. The tool quantifies the value of utilizing BR in this manner in terms of economic and environmental factors, including on-site and off-site electricity production and carbon taxes. This enables the tool to provide an optimization of the quantity of bauxite residue to be used based on the user’s specifications. The algorithm considers valorization of bauxite residue separately as both an ingredient in the raw meal and a supplementary cementitious material to maximize the opportunities to utilize the residue. The tool is designed to be used by users of both the alumina and cement industries and is compatible with the needs of each sector to consider the costs of commercialization, transportation, and cost-advantages of valorizing bauxite residue.